The Egypto-Aramaean Stela of Ahatabu (Berlin ÄM 7707): A Cross-Cultural Discussion - Wasmuth, Melanie (Die Welt des Orients, 2022)
The mortuary stela of a woman named Ahatabu, found in the Saqqara necropolis in Egypt, is a uniquely customized artefact that gives insight into the multicultural environment of Achaemenid Egypt (526-332 BCE). The woman and her family seem to have lived in Marea in the western Delta, possibly in a garrison complex. The stela contains two inscriptions, one written in Egyptian hieroglyphic script and the other in Aramaic. The stela design draws on a mixture of generic and highly customized features rooted in traditional Egyptian and arguably Yahwistic, (Egypto-)Phoenician, Aramaean, Egypto-Carian, Egypto-Ionian, and (Egypto-)Persian cultural traditions. Though unusual from an iconographic standpoint with respect to both comparable Egypto-Egyptian depictions and contemporary or slightly earlier Egypto-foreign stelae, the basic design of three registers spread over the whole stela while integrating the rounded stela top and the upper register is typical of a group of Egypto-Carian/Ionian stelae from Memphis. The inspiration may have come either from a contemporarily visible display in the necropolis or from actual designs within the various workshops. This article discusses the iconographic and epigraphic details of the stela in order to contextualize the artefact and its honorees within contemporary Egyptian design and funerary practices.